Proses Pembentukan Peraturan Daerah No. 5 Tahun 2021 Tentang Perlindungan dan Pemberdayaan Nelayan di Kabupaten Takalar Perspektif Dusturiyah - Fathan Mubina Ramadhan Hajir; Darussalam Syamsuddin; Sippah Chotban (Pusat Riset dan Inovasi Nasional, 2026)
This research discusses the role of the community in the formation of Regional Regulation (PERDA) Number 5 of 2021 in Takalar Regency from the perspective of siyasah dusturiyah. The aim of this research is to analyze: (1) the participation of fishermen in the formation of the PERDA, (2) the government's efforts in the protection and empowerment of fishermen, and (3) the dusturiyah perspective on the formation of the PERDA. The study uses a qualitative approach with field research methods, relying on interviews and observations as data collection techniques. Data processing is carried out through reduction and categorization, and its validity is tested through transferability, dependability, and credibility. The research findings show that fishermen have actively participated in activities organized by the local government. Protection and empowerment of fishermen are carried out in accordance with the mandate of PERDA No. 5 of 2021. The process of forming the PERDA is also in line with the principles of siyasah dusturiyah, such as alignment with the 1945 Constitution and national law, strengthening regional autonomy and decentralization, principles of welfare and social justice, as well as respect for human rights (HAM). Furthermore, it supports public participation, accountability, and the balance of economic development.